Novel Binary-Addition Tree Algorithm for Reliability Evaluation of Acyclic Multistate Information Networks - Yeh, Wei-Chang; Hao, Zhifeng; Forghani-elahabad, Majid; Wang, Gai-Ge; Lin, Yih-Lon (Reliability engineering & system safety, 2021)
•An improved binary-addition tree (BAT) algorithm is proposed.•BAT is simple to understand, easy to code, and flexible to made-to-fit.•A fast algorithm to calculate the for reliability evaluation of acyclic multistate information networks•BAT outperforms UGFM which is the best related algorithm from the experiments.•The time complexities of both BAT and UGFM are equal. Acyclic multistate information network (AMIN), a variant of multistate information network (MIN) that is not dependent on the conservation laws of flow, plays an important role in the current-day network communications because many modern network structures are based on AMIN, e.g., social networks, local area networks (LANs), and 4G/5G networks. An effective evaluation of the network reliability of an AMIN serves as a major and primary metric for determining the performance and quality of the overall network. The network reliability, which was shown to be NP-hard, has been successfully resolved by the universal generation function method (UGFM). However, the UGFM can only address small-scale problems owing to the limitations of the current-day computer memories. To overcome this problem, an improved and enhanced binary-addition tree algorithm (BAT) is proposed in this study to effectively evaluate and analyze the reliability of the AMIN. The performance of the proposed BAT is validated via a few examples.